The Importance and Chosen Techniques of Teaching Very Young Learners to Write in English - Babiarz, Mirosław; Zapała-Kraj, Marta (Journal of Education, Technology and Computer Science, 2019)
The aim of the following paper is to introduce the aspect of teaching writing to very young pupils. The paper briefly presents the characteristics of young learners, together with their needs and requirements – mostly referring to the teachers of English. The paper was based on author’s own experiences as the former teacher of very young and young students and so, it points out some useful techniques as well as personal observations rooted in the theory of methodology, which were successful in teaching English to that particular age group.